The Effects of Expiratory Muscle Strength Training on Swallowing and Voice Measures in Healthy Older Adults - (:unkn) unknown (My University, 2013)
This study investigated the effects of a four week expiratory muscle strength training (EMST) exercise program on healthy older adults (65-79 years). The investigators were interested in possible changes to the swallowing and voice production systems, both of which are in the scope of practice for a speech language pathologist. Specific voice variables included maximum phonation time, conversational intensity level, and upper and lower limits of available intensity range. Swallowing variables were related to tongue function and included maximum isometric pressure and mean swallowing pressure. Finally, maximum expiratory pressure was measured as a comparative value to other EMST studies. A Control group and a Treatment group were involved in this study, with both groups screened for any past history of speech, language, swallowing, or respiratory disorders. Pre-test to post-test significant differences were found between the Treatment and Control group for the upper limit of available intensity range and maximum expiratory pressure. The results indicate that older adults can increase their vocal volume following an EMST exercise program. Further research is necessary to evaluate other lingual strength and function variables, and effects of detraining following EMST device use.
Keywords: EMST; Expiratory Muscle Strength Training; Older Adults; Tongue Strength; Voice Production